An ‘early interval ’ (Delayed Urgent) laparoscopic cholecystectomy for acute cholecystitis: evidence to support a safe surgical procedure - Sakran, Imad F. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: Delayed interval cholecystectomy can be performed to overcome the logistical difficulties in performing ‘early urgent’ laparoscopic cholecystectomy (LC) within 72 hours of admission with acute cholecystitis (AC), and to avoid earlier re-admission with recurrent AC in patients waiting ‘delayed interval’ cholecystectomy. Objectives: To evaluate the safety and feasibility of ‘delayed urgent’ LC performed beyond 72 hours. Methods: Patients admitted with AC were scheduled for urgent LC. Patients who underwent ‘early urgent’ LC were compared with those who had ‘delayed urgent’ surgery. Results: Fifty consecutive patients underwent urgent LC for AC within 2 weeks of admission. There were no conversions and no bile duct injuries. Delayed surgery (n=36) neither prolonged operating time (90 vs. 85 minutes) nor increased operative morbidity (9.7% vs. 7.7%) or mortality (2.4% vs. 7.7%) compared with early surgery (n=14). Although delayed surgery was associated with shorter postoperative hospital stay (1 vs. 2 days, p=0.029), it prolonged total hospital stay (9 vs. 5 days, p<0.0001). Conclusions: Delay of LC beyond 72 hours neither increases operative difficulty nor prolongs recovery. It might be more cost effective to schedule patients who could not undergo ‘early urgent’ LC but are responding to conservative treatment for an ‘early interval’ LC within 2 weeks of presentation with AC.